Pengembangan Kualitas Kepribadian Guru - Oktradiksa, Ahwy (FITK UIN Walisongo, 2012)
Teachers play a role in improving the quality of education. As individuals, the teacher is the embodiment of all the unique characteristics according to its position as the teaching profession stakeholders. Personality is the primary foundation for self-realization as an effective teacher in carrying out their professional duties. This requires a teacher to be able to realize effective personal to carry out the functions and responsibilities. Teachers must know himself and is able to develop in the direction of the realization of a healthy personal and plenary. Teacher's personality is an important factor for the success of ter-learning students. Personality of the teacher becomes an example for their students. Teacher's personality into the factors that determine good or bad personality of the child. Good personality became a teacher requirements.Â Abstrak Guru memegang peran dalam peningkatan mutu pendidikan. Sebagai pribadi, guru merupakan perwujudan dari seluruh keunikan karakteristik yang sesuai dengan posisinya sebagai pemangku profesi keguruan. Kepribadian merupakan landasan utama bagi perwujudan diri sebagai guru yang efektif dalam melaksanakan tugas profesionalnya. Hal ini menuntut seorang guru harus mampu mewujudkan pribadi yang efektif untuk dapat melaksanakan fungsi dan tanggung jawabnya. Guru harus mengenal dirinya sendiri dan mampu mengembangkannya ke arah terwujudnya pribadi yang sehat dan paripurna. Kepribadian guru merupakan faktor terpenting bagi keberhasilan belajar anak didik. Kepribadian guru menjadi contoh bagi peserta didiknya. Kepribadian guru menjadi faktor yang menentukan baik atau buruknya kepribadian anak. Kepribadian yang baik menjadi persyaratan sorang guru. Kunci kunci: n.